Comparative Study of Left Ventricular Low Wall Motion with Scar Tissue Using 4D Left Ventricular Cardiac Images - Lee, Chien-Yi; Singh, Yashbir; Friebe, Michael; Hu, Wei-Chih (British Journal of Healthcare and Medical Research, 2018)
Myocardial contraction affects the cardiovascular pumping system, and helps in the early phase to detect abnormalities of wall motion noninvasively. In this research, we designed a program to characterize regional abnormalities because scar tissue is very difficult to identify in normal cardiac CT images. We created 10 frames of a 3D heart model that contains the long axis as reference for predicting the left ventricular wall motion. We tested our 4D cardiac model with scar tissue using non invasive cardiac CT images. Here, four subjects (patients) were involved in this study. Subject 1 and 4 are matching the low motion of surgical area with scar tissue area. Subject 2 found fibrous tissue regions (about 40%), compared with the 2SD (Standard Deviation) region. The fibrotic area is completely overlapped with a low-motion region which indicates the fibrotic area has a significant correlation with the low wall motion region. This research evaluates low wall motion of the left ventricle and detection of fibrosis regions.